Multimodality imaging-based evaluation of Rosai–Dorfman disease in the head and neck: A retrospective observational study. Issue 51 (December 2017) - Xu, Qinggang; Fu, Liping; Liu, Chengyao
Abstract : Abstract: Rosai–Dorfman disease (RDD) is an uncommon benign entity characterized histologically by lymphatic sinus dilatation due to histiocyte proliferation. This study was performed to delineate its imaging features, reviewed retrospectively in 12 patients (8 women and 4 men, mean age 58.2 years [range 27–84]) with pathologically confirmed RDD in the head and neck. The location, involvement, and imaging characteristics (CT, magnetic resonance imaging (MRI), and PET/CT) of all lesions were evaluated. Signal intensity on MRI images was compared to gray matter (orbital RDD) and adjacent muscle (sinonasal and cervical RDD). RDD in the head and neck involved multiple sites, primarily the sinonasal cavity (n = 7), neck (n = 3), and orbit (n = 1), with one case of simultaneous involvement of the sinonasal cavity, orbit, and neck. With sinonasal involvement, MRI signal intensity of the involved areas was isointense or slightly hyperintense relative to adjacent muscle on T1WI images and heterogeneous on T2WI images; with lacrimal involvement, it was isointense relative to gray matter on T1- and T2-weighted images; and with neck involvement, it was isointense relative to muscle on T1WI images and relatively hyperintense on T2WI images, with homogenous postcontrast enhancement in all sites of involvement. The lesions on CT were observed as enhancing masses with or without bony destruction. PET/CT showed hypermetabolism in one lesion in the neck. RDD is a rare disorder with multiple sites of involvement in the head and neck. Concomitant cervical lymphadenopathy with extranodal masses assisted by multimodal imaging may be useful in the diagnosis of RDD.